Estimation of Age from the Fusion of Human Sternum in ‘Bengalee’ Population from Dead Bodies Sent for Autopsy in NRSMCH Morgue - Sandip Mukhopadhyay; Sayak Sovan Dutta; Subhajit Adhikary (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Age is a datum of identification for any human individual.It is mandatory for an autopsysurgeon to perform autopsy of unknown dead bodies brought by the police, and the dilemma that he orshe faces is how to establish the identity of that body.Sternum is the bone which gives a fair idea for theestimation of age in the later decades of life. Method: the aim of the study is estimation of Age from thefusion of different parts of Sternum in a human individual.Dead bodies of ‘Bengalee’ persons sent forPost Mortem examination in the Hospital morgue, Department of Forensic Medicine & Toxicology, N.R.SMedical College & Hospital, Kolkata. 120 sternums are studied in this study over a period of 1.5 years.Fusion of xiphisternum with the lower end of mesosternum starts above 22 years of age, complete unioncan be observed above 31 years on the other hand beginning of union can also be seen at 45 years of age.No union or beginning of union was seen in older ages also.Complete fusion between manubrium and upperend of mesosternum was found at as low as 24 years age,yet beginning of union and recently complete unionwas seen at 40 years and 47 years- 49 years respectively. Older ages also showed no union. There was nosignificant difference between male and female in respect to the ages showing fusion.The increasing gradesof fusion of different sternal segments when compared with increasing ages showed significant statisticalcorrelation. Conclusion: In the ‘Bengalee’ population it can be said that with increasing age the differentparts of sternum show increasing grades of fusion, fusion of the sternebrae startsaround puberty and iscompleted by 17 years- 20 years of age, xiphoid process fuses next and then comes the fusion betweenmanubrium and mesosternum, though exceptions are there, where younger aged individuals showedcomplete union yet older aged individuals showed no union or beginning of union.